New record of Rhagomys rufescens (Thomas 1886) (Rodentia: Muridae: Sigmodontinae) in the Atlantic forest of southeastern Brazil - Pinheiro, Paula S.; Hartmann, Paulo A.; Geise, Lena (Zootaxa, 2004)
Rhagomys rufescens is a threatened Sigmodontinae rodent from the Atlantic forest of southeastern Brazil, known by a few specimens deposited in scientific collections. This work presents a new record of this species, collected in Parque Estadual da Serra do Mar N cleo Picinguaba (Ubatuba, SP) in April 2002, and some biological data. This finding reinforces the urgency of improving collecting efforts in Atlantic forest, in order to know and preserve its biodiversity.